2019
DOI: 10.4018/ijehmc.2019010106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Early Adopter Baby Boomers' Approach to Managing Their Health and Healthcare

Abstract: The Patient 3.0 Profile is used to explore to the patient engagement strategies of early adopter baby boomers' in three domains: 1) patient relationships, 2) health information use and 3) consumer health technology (CHT) use. Findings from six focus groups with early adopter boomers challenge prior notions about older adults' passive approach to patient engagement. Baby boomers want to make final healthcare decisions with input from providers. While adept at finding and critically assessing online health infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…They use OHS frequently, but only for information-seeking and not for diagnosis, treatment or disease management. Another study from the US [13] showed that intergenerational interactions in which older adults were mentored by college students resulted in a significant drop in technophobia and major improvements in OHS literacy, self-efficacy and interest in technology.…”
Section: Introductionmentioning
confidence: 99%
“…They use OHS frequently, but only for information-seeking and not for diagnosis, treatment or disease management. Another study from the US [13] showed that intergenerational interactions in which older adults were mentored by college students resulted in a significant drop in technophobia and major improvements in OHS literacy, self-efficacy and interest in technology.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings make unique contributions to PHIM descriptions, with the introduction of health finance management as a major PHIM goal for health care consumers. To date, research has been limited to health care consumers’ ability to understand and use insurance information effectively [ 52 , 53 ], their management of out-of-pocket expenses [ 11 , 24 , 54 ], and their desire to talk to their health care providers about health care costs [ 11 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were able to engage the services of professional organizers, and managing financial PHI (including insurance) was emphasized in PHIM work. Our approach purposefully removed economic constraints to better understand the challenges that remain around patient engagement [ 11 , 13 ] and PHIM work for older adults. Therefore, caution should be exercised when transferring our findings to uninsured and low-resource groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations